Appraisement and benchmarking of third-party logistic service provider by exploration of risk-based approach - Nitin Kumar Sahu; Atul Kumar Sahu; Anoop Kumar Sahu (Cogent Business & Management, 2015)
In the present era, Reverse Logistics Support has monitored as a momentous realm, where stuffs are transferred from point of consumption to origin. The companies who provide the logistic equipments, i.e. Truck, Joseph Cyril Bomford, and Shipment, etc. to its partner's firms called Third-Party Logistics (3PL) service provider. Today, the feasible 3PL service provider evaluation-opt problem is yet an amorous dilemma. The appraisement and benchmarking of logistics service providers in extent of index; allied risk-based indices and their interrelated metrics; outlooked as a great tool for each international firm, in order that firm could obtain their core goals. The novelty of manuscript is that here, a hairy-based approach has been integrated and then implemented upon a novel developed multi hierarchical third-party logistics (3PL) service providers appraisement index in purpose to umpire the 3PL provider for their strong and ill's core indices. Moreover, the overall score (Si) system has also been carried out for benchmarking the 3PL provider companies, where s1 has been found as the best 3PL service provider. The developed approach enabled the manager of firms to make the verdict towards the best inclusive evaluation process of 3PL performance appraisement and benchmarking. A numerical illustration has also been provided to validate the verdict support system.
Keywords: 650